The Influence of Coordination of Effectiveness of Publishing Fatwa Locations In Board of Investment and Central City Integrated Licensing Services - Tine Badriatin; Deni Sudrajat; Lucky Radi Rinandiyana (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2021)
Coordination has an important role in achieving the effectiveness of employees in an organization. As of this research is to study and analyze the effectiveness of coordination Influence Publishing Fatwa Locations in Board of Investment and Integrated Licensing Services Banjar. The method used in this research is explanatory research study. The population in this study were employees at the Board of Investment and Integrated Licensing Services Banjar, with a sampling technique that is the census that all employees in the Board of Investment and Integrated Licensing Services Banjar, with a total of 32 people, not including the Head BPMPPT. Based on the results of the study showed that each of the terms of coordination covering Sense of Cooperating, Rivalry, Team Spirit, Esprit de Corps, has contributed to the effectiveness of the issuance of Fatwas location by the Board of Investment and Integrated Licensing Services Banjar, so by testing hipoteis shows overall ( simultaneous) on the terms of coordination on the effectiveness Publishing Fatwa Locations in Board of Investment and Integrated Licensing Services Banjar.